2017
DOI: 10.3389/fpsyg.2017.00814
|View full text |Cite
|
Sign up to set email alerts
|

White Lies in Hand: Are Other-Oriented Lies Modified by Hand Gestures? Possibly Not

Abstract: Previous studies have shown that the hand-over-heart gesture is related to being more honest as opposed to using self-centered dishonesty. We assumed that the hand-over-heart gesture would also relate to other-oriented dishonesty, though the latter differs highly from self-centered lying. In Study 1 (N = 79), we showed that performing a hand-over-heart gesture diminished the tendency to use other-oriented white lies and that the fingers crossed behind one’s back gesture was not related to higher dishonesty. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This finding can also be discussed in the context of prosocial effects of serotonergic treatments. There are various studies showing that serotonergic medicaments like MMDA or Citalopram may positively affect social cognitive parameters like empathy, emotion recognition and moral behaviours (Cantarero et al, 2017;Hysek et al, 2014). These findings may explain positive effects of SSRI medicaments in PE treatment in relation to social cognitive profiles of these patients, as current study reveals the significant deficits of PE patients in such domains.…”
Section: Discussionsupporting
confidence: 55%
“…This finding can also be discussed in the context of prosocial effects of serotonergic treatments. There are various studies showing that serotonergic medicaments like MMDA or Citalopram may positively affect social cognitive parameters like empathy, emotion recognition and moral behaviours (Cantarero et al, 2017;Hysek et al, 2014). These findings may explain positive effects of SSRI medicaments in PE treatment in relation to social cognitive profiles of these patients, as current study reveals the significant deficits of PE patients in such domains.…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, we tested preference for overly positive feedback vs. the blatant truth in a virtual context. Cantarero et al (2017) found that when individuals were asked to give their opinion regarding a picture, they provided more positive feedback to the alleged author of the work in person, than when the opinion was gathered privately in writing. It would be interesting to see if in face-to-face communication, desire to excel and ability to handle failure exerted the same effect on preference toward prosocial lies as in the online setting.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that people tend to use less self-oriented lies to the ones they are close to (DePaulo et al, 1996). However, the literature also shows a positive link between lying and liking, yet only when the liar intends to benefit others (e.g., Cantarero et al, 2017). The relationship between liking and cheating found in this study might therefore be a case of spurious correlation stemming from the fact that mimicry tends to increase the liking of the mimicker.…”
Section: Discussionmentioning
confidence: 99%